Between utilitarian and autonomous: Polish opera in the second half of the nineteenth century - Zieziula, Grzegorz (De musica disserenda, 2015)
The Warsaw premiere of Moniuszko’s Halka (1858) opened the way to more ambitious operatic works in Poland. Operas written towards the end of the century, among them Livia Quintilla by Zygmunt Noskowski and Philaenis by Roman Statkowski, were deliberate statements of artistic autonomy. They prepared the ground for the operatic compositions of the generation of Karol Szymanowski.